2021
DOI: 10.2166/wst.2021.626
|View full text |Cite
|
Sign up to set email alerts
|

Study on the properties of denitrifying carbon sources from cellulose plants and their nitrogen removal mechanisms

Abstract: Carbon sources of cellulose plants are the promising materials that enhancing the activities of denitrifying bacteria in the groundwater system. To further verify the denitrification performance of cellulose plants and the main factors of affecting the denitrifying system, six cellulose plants from agricultural wastes (wood chip, corn cob, rice husk, corn straw, wheat straw, and sugar cane) were selected for bioavailable organic matter leaching experiments, carbon denitrification experiments, functional bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The average chemical oxygen demand (COD) concentration observed was 190.65 ± 26.74 mg/L, showing a diminishing trend over time with fluctuations ranging from 150.83 mg/L to 216.67 mg/L. These findings align with other studies using agricultural residues, such as wood chips, corn cobs, rice husks, corn straw, wheat straw, sugarcane straw [56], Typha angustifolia [57], and sugarcane straw [19]. These studies similarly reported an initial release of carbon followed by a gradual decrease.…”
Section: Leaching Assaysupporting
confidence: 86%
“…The average chemical oxygen demand (COD) concentration observed was 190.65 ± 26.74 mg/L, showing a diminishing trend over time with fluctuations ranging from 150.83 mg/L to 216.67 mg/L. These findings align with other studies using agricultural residues, such as wood chips, corn cobs, rice husks, corn straw, wheat straw, sugarcane straw [56], Typha angustifolia [57], and sugarcane straw [19]. These studies similarly reported an initial release of carbon followed by a gradual decrease.…”
Section: Leaching Assaysupporting
confidence: 86%
“…Zhang et al conducted an analysis of 10 different types of straw leaching solutions, and discovered that the primary constituents were organic acids, carbohydrate and nitrogenous organics, which contained a total of 16 compounds [32]. Similarly, Qi et al carried out experiments on six different types of straw and found that cellulose extracts contained a mixed carbon source system including small molecular organic acids, sugars, nitrogen-containing organic components and esters [33]. However, these studies have their limitations when it comes to component analysis.…”
Section: Component Analysis Of the Enzymatic Scsmentioning
confidence: 99%